Decreased erythrocyte nucleoside transport and hENT1 transporter expression in glucose 6-phosphate dehydrogenase deficiency. Issue 1 (December 2015) - Al-Ansari, Mohammad; Craik, James
Abstract Background Glucose-6-phosphate dehydrogenase (G6PD) deficiency is associated with erythrocyte sensitivity to oxidative damage and hemolytic crises. In β-thalassemia major, where hemoglobin instability imposes oxidative stress, erythrocytes show reduced hENT1 nucleoside transporter expression and decreased nucleoside uptake. This study investigated hENT1 expression and nucleoside transport in G6PD-deficient erythrocytes to determine if decreased hENT1 activity might be a contributory feature in the variable pathology of this enzymopathy. Methods Uptake of3 H-uridine was measured at room temperature using an inhibitor-oil stop protocol and 5-s incubations. Erythrocyte membranes were analyzed by SDS-PAGE and nucleoside (hENT1), glucose (GLUT-1), and anion exchange (Band 3) transporter polypeptides quantitated on immunoblots. Results In G6PD-deficient cells, uridine uptake (mean 8.18, 95 % CI 5.6–10.7 vs controls mean 12.35, 95 % CI 9.2–15.5, pmol uridine/gHb/min;P  = 0.031) and expression of hENT1 (mean 50.4 %, 95 % CI 38.1–62.7 %, arbitrary unitsn  = 11 vs controls mean 95.23 %, 95 % CI 88.38–102.1 % arbitrary units, n  = 8;P  < 0.001) were significantly lower; expression of GLUT-1 (mean 106.9 %, vs control mean 99.75 %;P  = 0.308) and Band 3 polypeptides (mean 100.1 %, vs control mean 102.84 %;P  = 0.329) were unchanged. Conclusions Nucleoside transporter activity in human erythrocytes sustains intracellular purine nucleotide levels and assists in control of plasma adenosine levels; decreased hENT1 expression and activity in G6PD-deficiency could affect red metabolism and influence a wide spectrum of responses mediated by adenosine receptors.